KEPEMIMPINAN DAN KEPUASAN KERJA PEGAWAI PADA DINAS PERINDAGKOP & UKM KABUPATEN KUATAI BARAT - Adi Suroso, Meta Yunina Bela, Theresia Militina (EKONOMIA, 2016)
This study aims to determine the leadership style directive and participative leadership style on job satisfaction of employees in the department Perindagkop and UKM West Kutai Barat, as well as to determine the variables the dominant influence on employee job satisfaction. The population in this study are employees of agencies Perindagkop and UKM West Kutai amounted to 38 employees . The sampling technique conducted a census ( all population sampled ). Data collection techniques done by field research in the form of questionnaires and direct observations, as well as literature. Model analysis used is multiple linear regression, hypothesis testing using a tool with F test and t test, tools application program SPSS. The correlation coefficient R is 0,797, interpretation of multiple correlation coefficient in the interval from 0,60 to 0,79 that is at the level of a strong relationship between the leadership style of directive and participative leadership style on job satisfaction of employees. The coefficient of determination of 0,636 means that the directive style of leadership and participative leadership style has amounted to 63,60 % influence on job satisfaction of employees in SMEs Perindagkop and Kutai Barat , while the remaining 36,40 % influenced by other variables that are not included in this research. Based on the test results F = 30,518 with a significant level of 0,000 < α = 0,05, thus directive style of leadership and participative leadership style is jointly significant effect on job satisfaction ( Y ) employees at Perindagkop and UKM Kutai Barat. T test results showed beta value of 0,274 with 0,064 significance level value of alpha ( α ) = 0,05 means the directive leadership style not significant effect on employee job satisfaction. T test for beta 0,571 with a significance level of 0,001 < α = 0,05 in other words, a significant and dominant influence on employee job satisfaction ( Y ) Perindagkop and UKM Kutai Barat , this means that the researchers propose the hypothesis is accepted.